O gênero entre arenas e alianças: planos municipais de educação em municípios da região central do RS - Perlin, Lidiane Londero (2023)
It is understood that the sex/gender system refers to what was socially constructed, in order to make subjects assume a certain role and/or performance based on what is usually called biological sex. As a product and producer of this social, the educational system projects certain expectations and sayings onto bodies, which makes what can and cannot be said about gender and sexuality being constantly under tension. That said, the problem is “how do Municipal Education Plans in the central region of Rio Grande do Sul produce discourses that manage and inhibit notions of gender and sexuality, constituting an educational field in dispute?”. For this purpose, the research is based on the cartographic analysis of educational policies based on the Policy Cycle, particularly the contexts of influence and the contexts of text production, according to studies by Stephen John Ball. The Municipal Education Plans under analysis come from four municipalities, among the 33 that are part of the Association of Municipalities of the Central Region of the State (AMCentro), and this selection was based on population numbers, with the two most populous municipalities (Santa Maria and Cachoeira do Sul) and the least populous (Ivorá and Unistalda). In addition to analyzing the PMEs, the cartographic movement made it possible to search for news records linked to gender and sexuality issues on the municipal websites and/or other media. As a result, the research findings call for two units of analysis: "the arena as a possibility" and "alliance as [in]visibility". These units of analysis gradually emerge in the course of the writings and address discourses on the notions of gender and sexuality, highlighting the educational field as a territory of disputes. That said, the proliferation of discourses around the PMEs alludes to the conflict and clash over the themes-notion of gender/sexuality and the possible folds in which these issues find an echo. The analysis here reverberates to the very terrain of insecurity in education policy, which incessantly creates and recreates arenas and, at the same time, requires unpredictable alliances.